Good and Bad Effects of Online Teaching on Today’s Youth DuringCovid-19 - T. Swetha,; Mir , Nazir Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
This paper deals with the effects of online teaching during pandemic situation which has been worst in recent time.  It also aims to give a vivid picture on the good and bad effects of online teaching on today’s youth.As a coin has two sides, the online teaching also has its own merits and demerits. The process of teaching also becomes the toughest job. Online teaching has been a common platform from a child to an adult for learning.Of course, the traditional teaching is replaced by the online teaching. But the traditional classroomcannot be replaced by the digital teaching. The study gathers the information about the interaction between the teacher and the learner and their relationship with digital classroom.It also gives the information how the learners receive it.The importance of online teaching is recognized by the government at this present crisis and encourage the online teaching for continuous learning. The study even takes the quantitative method for the surveys and feedback. The studyproves that online teaching is effective not only on adults but also on the young people.